Islamic Literature and “Islami” Literature in Contemporary Indonesian Literature - Affurqand, Muhammad Daffa; Zakiatir; Na’in, Rizky Nabil Setyawan; Al Ayubi, Muhammad Ryamizard (Proceedings of International Conference on Islamic Civilization and Humanities, 2025)
The use of the terms Islamic Literature (Sastra Islam) and Islami Literature (Sastra Islami) among both literary scholars and literature enthusiasts in Indonesia remains ambiguous. This confusion is partly due to the development of Islam in Indonesia after the New Order era, during which publishers began unilaterally claiming their works as Islamic Literature or Islami Literature. Based on this context, the present study aims to define and distinguish the characteristics of these two terms. This research uses the dialectical method, which involves contrasting differing views on a particular issue—in this case, the definitions of Sastra Islam and Sastra Islami. Data collection was carried out through literature review, focusing on scholarly opinions, literary critics, literary texts, and the development of Indonesian literature. The findings indicate that Sastra Islam refers to literary works strictly grounded in scriptural texts such as the Qur’an and Hadith, whereas Sastra Islami is more fluid and does not necessarily adhere to scriptural foundations.